System immunoinformatics–based design of a multi-epitope vaccine candidate against La Crosse virus - Md. Habib Ullah Masum; Homaira Pervin Heema; Ahmad Abdullah Mahdeen; Syed Mohammad Lokman; Zarin Tasnim; Md. Rakibul Hasan; Sanjida Hossain Arpa; Rehana Parvin; Jannatul Ferdous; Mohammad Sharif Uddin (PLoS ONE, 2026)
The emergence of La Crosse virus (LACV) infection has been attributed to the global expansion of mosquito habitats and climate change. This pressing issue underscores the urgency of preemptive actions to combat the infection. Currently, no vaccines or targeted antivirals are available for LACV infection. The present study utilizes advanced immunoinformatics approaches for the design of a multiepitope vaccine (LACV-mVax01) targeting the viral proteins G1, G2, and N. The structural assessment suggested favorable stability characteristics, reflected by an instability score of 17.12 and an aliphatic index of 81.88. Based on the two-dimensional structure, the LACV-mVax01 had an alpha-helical content of ~45%, with favorable beta sheets and coils. The refinement of the LACV-mVax01 resulted in an accurate model (TM-score 0.49, C-score −1.86), supported by high-quality metrics (RMSD 0.489, MolProbity 2.230, ERRAT 85.539). Docking analyses indicated potential binding interactions with TLR4, showing a binding energy of −1000.0 compared to −939.2 for TLR2. Molecular dynamics simulations were consistent with these observations, suggesting relatively stable interactions and maintenance of structural integrity in both complexes. Codon optimization yielded a codon adaptation index of 0.9848, and the predicted mRNA structure had a free energy of −342.16 kcal/mol, consistent with a stable conformation. Subsequent in silico immunological analyses suggested humoral and cellular responses, including probable memory B- and T-cell responses. However, sustained immunity was also supported by consecutive cytokine and antibody synthesis. The comprehensive structural, molecular, and immunological evaluations suggest that LACV-mVax01 is a promising vaccine candidate capable of eliciting sustained protective immunity against LACV infection. Though future in vitro , in vivo , and clinical validations are required to perceive its effectiveness and safety.